PENERAPAN MODEL STUDENT TEAMS ACHIEVIEMENT DIVISIONS (STAD) PADA PEMBELAJARAN IPS SISWA KELAS IV SD NEGERI 2 PETUNANG - Miko Yensi; Andriana Sofiarini; Andri Valen (Primary Education Journal Silampari (PEJS), 2022)
The research objective was to find out using the Student Teams Achieviement Divisions model in social studies learning for grade IV Elementary School 2 Petunang students significantly complete. The research method used was quasi-experimental, the research design was pretest-posttest group design. The population was all students in grade IV Elementary School 2 Petunang and a sample of 22 students in grade IV which was determined by simple random sampling. The data collection technique used a test technique in the form of 7 essay questions. The average final test score of students was 76.62 with the percentage of the number of students who completed 59.09%. The collected data were analyzed using the t test. based on the results of t-test analysis at a significant level α = 0.05, the value obtained is tcount (1.93) ≥ t_ (table) (1.72), because tcount ≥ t_ (table), it can be concluded that the social studies learning outcomes of students use The Students Teams Achieviement Divisions' learning model was significantly complete. Keywords: Model Student Teams Achieviement Divisions, Social Studies Learning, Learning Outcomes.